Using a Targeted Proteomics Chip to Explore Pathophysiological Pathways for Incident Diabetes– The Malmö Preventive Project - Molvin, John; Pareek, Manan; Jujic, Amra; Melander, Olle; Råstam, Lennart; Lindblad, Ulf; Daka, Bledar; Leósdóttir, Margrét; Nilsson, Peter M.; Olsen, Michael H.; Magnusson, Martin (Scientific reports, 2019)
Multiplex proteomic platforms provide excellent tools for investigating associations between multiple proteins and disease (e.g., diabetes) with possible prognostic, diagnostic, and therapeutic implications. In this study our aim was to explore novel pathophysiological pathways by examining 92 proteins and their association with incident diabetes in a population-based cohort (146 cases of diabetes versus 880 controls) followed over 8 years. After adjusting for traditional risk factors, we identified seven proteins associated with incident diabetes. Four proteins ( Scavenger receptor cysteine rich type 1 protein M130 , Fatty acid binding protein 4, Plasminogen activator inhibitor 1 and Insulin-like growth factor-binding protein 2 ) with a previously established association with incident diabetes and 3 proteins ( Cathepsin D , Galectin-4, Paraoxonase type 3 ) with a novel association with incident diabetes. Galectin-4 , with an increased risk of diabetes, and Paraoxonase type 3 , with a decreased risk of diabetes, remained significantly associated with incident diabetes after adjusting for plasma glucose, implying a glucose independent association with diabetes.